OPTIMASI KOMBINASI NAA, BAP DAN GA3 PADA PLANLET KENTANG SECARA IN VITRO - Larekeng, Siti Halimah (Journal Galung Tropika, 2012)
The research held in Agricultural Biotechnology Laboratorium of Hasanuddin University Research Center on January-October 2009. This research aimed to know the effect of NAA, BAP and GA3 combination to potato growth in vitro. We hope that the result could be use as information to develop qualified potato seed production through in vitro. This research used Complete Randomized Design with NAA, BAP and GA3 combination treatment. The treatments were kontrol, NAA 0,01 mg L-1 + BAP 0,05 mg l-1 + GA3 0,1 mg l-1 , NAA 0,01 mg l-1 + BAP 0,05 mg l-1 + GA3 0,2 mg l-1 ), R3 (NAA 0,01 mg l-1 + BAP 0,1 mg l-1 + GA3 0,1 mg l-1 ), R4 (NAA 0,01 mg l-1 + BAP 0,1 mg l-1 + GA3 0,2 mg l-1 ), R5 (NAA 0,1 mg l-1 + BAP 0,05 mg l-1 + GA3 0,1 mg l-1 ), R6 (NAA 0,1 mg l-1 + BAP 0,05 mg l-1 + GA3 0,2 mg l-1 ), R7 (NAA 0,1 mg l-1 + BAP 0,1 mg l-1 + GA3 0,1 mg l-1 ), R8 (NAA 0,1 mg l-1 + BAP 0,1 mg l-1 + GA3 0,2 mg l-1 ). Each treatment consists of 2 experiment units. Each treatment has 3 replication so there were 54 experiment units. The result showed that NAA 0,1 mg l-1 + BAP 0,1 mg l-1 + GA3 0,1 mg l-1 combination gave the best potato growth in number of twigs, number of leaves and planlet height.